The Gulf in World History Arabia at the global crossroads - Fromherz, Allen James (Edinburgh University Press, 2020)
The Gulf sits at an ancient crossroads of cultures and faiths, and at the heart of modern trade stretching back to the origins of civilization. As a site of both conflict and peaceful encounter, it can be studied in the context of world history, as a place of cultural and historical interaction. From medieval astrology to museum architecture, from the trade of glass and pearls to the role of Indians, Africans, Christian monks, Mandaeans and merchants, this book spans historical periods and disciplinary approaches. It is united by one overarching theme: the Gulf as a cosmopolitan nexus and space of encounter. The chapters describe a Gulf simultaneously perched on the edge of empires and at the centre of world events. Presenting new evidence, new theoretical approaches, and new arguments, this volume aims to change understandings of the Gulf in the world.